What are practitioners' views of how digital health interventions may play a role in online child sexual abuse service delivery? - Quayle, Ethel; Schwannauer, Matthias; Varese, Filippo; Cartwright, Kim; Hewins, Will; Chan, Cindy; Newton, Alice; Chitsabesan, Prathiba; Richards, Cathy; Bucci, Sandra (Frontiers in Digital Health, 2024)
Introduction Online child sexual abuse (OCSA) affects considerable numbers of children globally and is associated with a variety of mental health problems. Existing practitioner studies suggest that young people are infrequently asked about online abuse and practitioners have a fragmented understanding of the problems experienced or how they might approach them. There are very few evidence-based interventions that guide clinical assessment or practice. Digital Health Interventions (DHIs) have the potential to be an effective option where children and young people's services are challenged, including accessibility and anonymity. The aim of this study was to explore mental health practitioners' views of how DHIs may play a role in supporting young people who have experienced OCSA, and the role they can play in healthcare delivery. Method In-depth qualitative interviews and one focus group were conducted with 25 child mental health professionals across two sites (Manchester and Edinburgh). Data was analyzed using reflexive thematic analysis. Results Three overarching themes and 9 sub-themes were identified: (1) feeling a little bit lost; (2) seeing potential problems; and (3) knowing what works. Practitioners expressed interest in a DHI to support this client group and saw it as a way of managing waiting lists and complementing existing therapies. They felt that many young people would see this as a preferred medium to in-person therapy, would be empowering, and offers new ways of learning how to stay safe online. However, there were concerns about how much time would be needed by staff to deliver a DHI, anxieties about safety issues in relation to content and data protection, some of which may be unique to this population of young people, and concerns about the absence of a therapeutic relationship with vulnerable children. Discussion Our findings indicated that practitioners were uncertain about working with children subjected to OCSA but were receptive to the possibility of using a DHI to support their practice and to reduce waiting lists. Concerns were expressed about the time needed for staff training and support as well as concerns over patient safety and the lack of evidence about the effectiveness of an unsupported DHI.